A single-center study on total mastectomy versus skin-sparing mastectomy in case of pure ductal carcinoma in situ of the breast. Issue 6 (June 2019) - Lhenaff, Margaux; Tunon de Lara, Christine; Fournier, Marion; Charitansky, Hélène; Brouste, Véronique; Mathoulin-Pelissier, Simone; Pinsolles, Vincent; Rousvoal, Aurelien; Bussieres, Emmanuel; Chassaigne, Florence; Croce, Sabrina; Ben Rejeb, Houda; et al.
Abstract: Introduction: Ductal carcinoma in situ (DCIS) accounts for 15% of all breast cancers and generally, the prognosis is good if treated optimally. The standard treatment includes breast conservative surgery along with adjuvant radiotherapy. Skin-sparing mastectomy (SSM) preserves the breast skin envelope but its oncological safety poses a few concerns. Moreover, no DCIS-specific studies have compared the local recurrence (LR) rate following total mastectomy (TM) or SSM. We evaluated the LR rate in DCIS patients who underwent either TM or SSM. Methods: This is a retrospective study on women who underwent mastectomy with or without immediate breast reconstruction or secondary reconstruction for pure DCIS of the breast. All patients treated at Institut Bergonié by mastectomy for DCIS from January 1990 to December 2010 were included. LR and overall survival (OS) rates were estimated. Results: The study population included 399 patients who were categorized into two groups, 207 in the TM group and 192 in the SSM group. At 10 years of follow-up, the LR rate was 0.97% in the TM group and 1.04% in the SSM group (p = NS). The OS of the entire population was 94.7% [95% CI; 91.6–96.7], 92.8% [95% CI, 87.9–95.8] for the TM group and 96.8% [95% CI, 91.6–98.8] for the SSM group. Conclusions: In our study, the LR rate following mastectomy is low, regardless of the surgical technique used, with an excellent OS at 10 years.